Rheolytic thrombectomy in patients with acute ST segment elevation myocardial infarction and large thrombus burden - Mohammed Hosny Ahmed Awad; Amr Abdelaziz Elfaramawy; Magdy Abdelhamid Abdelaziz; Magdy Habib Yacoub (Cairo : Mohammed Hosny Ahmed Awad, 2018)
Background : Controversial data exist regarding the potential benefits of use of Rheolytic thrombectomy (RT) in patients with ST segment elevation myocardial infarction (STEMI) before infarct artery stenting. Purpose: To determine whether RT to the culprit vessel before conventional percutaneous coronary intervention (PCI) results in improved myocardial salvage index (MSI) assessed by cardiac magnetic resonance imaging (CMR) compared to conventional PCI only in patients with STEMI and large thrombus burden Methods: This was a randomized controlled, 2-arm, single center, prospective study conducted on patients with acute STEMI and large thrombus burden (TIMI thrombus grade 4 and 5) indicated for primary PCI. Patients with cardiogenic shock, culprit vessel size less than 2.5 mm or received thrombolytic therapy were excluded. Baselines CMR (within 48 hours after PCI) then follow up CMR after 3 months were performed to obtain MSI [MSI = (percent of the total area at risk {u2013} percent of total final infarct size) / the percent of total area at risk], microvascular obstruction (MVO) and final infarct size. The primary end point of the study was CMR-derived MSI at 3 months. The secondary end points were: corrected TIMI frame count (cTFC) and ST-segment resolution (STR) defined as a reduction in ST-segment elevation {u2265}50% at 30 minutes after infarct artery recanalization. Results: Eighty patients were randomly assigned on 1:1 basis to RT before conventional PCI (38 patients); RT group or conventional PCI only (42 patients);conventional PCI group. The mean age was 55 years; 75% male. There was no significant difference between both study groups regarding door to device time [60(30-130) min in RT group and 55(20-155) min in the conventional PCI group p=0.19]
Thesis (Ph.D.) - Cairo University -Faculty of Medicine - Department of Cardiology
Issued also as CD
Keywords: Large thrombus burden; Rheolytic thrombectomy; ST segment elevation myocardial infarction (STEMI)